Analisis Perceived Quality dan Perceived Value terhadap Intention to Subscribe pada Layanan Video on Demand Viu - Kartika, Dini; Komariah, Kokom; Mulia Z, Faizal (Peneliti.net, 2023)
Paid video service industry during the Covid-19 pandemic as the government advised the Large-Scale Social Restrictions (PSBB) for people to stay home that made them unable to go to cinema to watch films experience d a rapid rise. However, with the presences of more and more paid video apps competing in the market, the competitiveness has been getting tighter. Hence, an application named Viu has not always been the main choice for people that has led to the declining interest in the subscription of Viu application. The research was aimed at determining Perceived Quality and Perceived Value toward Intention to Subscribe on Viu Demand service of Viu application. The method applied in the research was quantitative method with causal-descriptive approaches. The technique of analysing data questionnaires. The technique of analysing data deployed was multiple linear regression analysis with the help os SPSS 26 software. The result of coefficient of determination test showhs that the value (R Square) obtained is amounted to 0.597, indicating that there is a relationship between Perceived Quality and Perceived Value towards Intention to Subscribe on Viu the video on demand application service by 59,7%, while the rest of 40,3% is determined by other variables not ecamined in the research. Perceived Quality (X1) influences Intention to Subscribe (Y) as proven by the value Tcount namely 2.529, largee than that of Ttable namely 1.65 With significance level of 0.12>0.05. Therefore, there is a significant influence from independent variable towards dependent variable